Development of resistance of some klebsiella species isolated locally - Baghdad Science Journal (مجلة بغداد للعلوم)
200 samples collected Adrar of patients with urinary tract infection were investigating the types of bacteria most local isolates showed high resistance to antibiotics penicillin c ??????? Amoxicillin Beracelin